In Situ Coupling FeM (M = Ni, Co) with Nitrogen‐Doped Porous Carbon toward Highly Efficient Trifunctional Electrocatalyst for Overall Water Splitting and Rechargeable Zn–Air Battery. (22nd May 2017) - Zhong, Hai‐Xia; Wang, Jun; Zhang, Qi; Meng, Fanlu; Bao, Di; Liu, Tong; Yang, Xiao‐Yang; Chang, Zhi‐Wen; Yan, Jun‐Min; Zhang, Xin‐Bo
Abstract : Electrocatalysts for hydrogen evolution reaction (HER), oxygen evolution reaction (OER), and oxygen reduction reaction (ORR) are crucial for water splitting and fuel cells/metal–air batteries, of which the benchmark catalysts for HER/ORR and OER are expensive and scarce Pt‐based and Ir/Ru‐based compounds, respectively. In spite of this, no trifunctional electrocatalyst for HER, OER, and ORR with an acceptable performance have been reported. In response, herein, as a proof‐of‐concept experiment, this study first in situ couples element abundant FeM (M = Ni, Co) particles with the nitrogen‐doped porous carbon (NPC) by a facile and scalable strategy. Unexpectedly, the resulted FeM/NPC exhibits superior trifunctional catalytic activities for HER, OER, and ORR even in the same electrolyte, which can be attributed to the synergistic advantages of FeM/NPC in terms of its good conductivity, highly porous structure, high Brunauer−Emmett−Teller (BET) surface area, nitrogen doping, and the intimate contact of FeM and NPC. Furthermore, such trifunctional catalyst makes the overall water splitting work at moderate overpotential, and endows the assembled Zn−air battery with a good performance and impressive capacity to self‐power the overall water splitting, demonstrating its feasibility for practical application. Abstract : In situ anchoring FeM (Ni/Co) alloy on a nitrogen‐doped porous carbon hybrid exhibits appreciable trifunctional electrocatalytic performances for oxygen evolution reaction, hydrogen evolution reaction, and oxygen reduction reaction in alkaline medium, thus making the overall water splitting and operation of the Zn‐air battery convenient, demonstrating its feasibility for practical application.